Gaze, Conversational Structures, and Mediation in Chilean Primary Education - Livacic-Rojas, P; Villalta-Paucar, M; Rebolledo-Etchepare, J (UNIV AUTONOMA BAJA CALIFORNIA, INST INVESTIGACION & DESARROLLO EDUCATIVO, 2025)
The aim of this study is to analyze the relationship between conversational structures, mediation criteria, and eye movements of teachers working in different socioeducational contexts in Chilean primary classrooms. A mixed-methods approach was used with a quantitative focus, which included the use of multivariate analysis and within-subject tests. The study included 40 teachers from 24 elementary schools: 11 schools in the urban area of the Santiago Metropolitan Region and 13 rural schools in Araucania. Actual lessons were filmed using eye-tracking lenses; the teachers gaze behavior was analyzed in classroom exchanges with and without the presence of criteria of Reuven Feuerstein s mediated learning experience theory. The results indicate that gaze towards students is greater in exchanges with mediated learning experience criteria, compared to those without, and gaze duration on students or their materials is greater in rural classrooms.